Congestive Heart Failure - Zahratun Humaira; Rivhan Fauzan (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Heart failure is a collection of clinical findings due to structural and functional disorders of ventricular filling and blood ejection. Heart failure can be caused by various medical conditions, including hypertension and myocardial infarction. In addition, heart failure can also be caused by congenital abnormalities, kidney disorders, lung disorders, infections, autoimmune diseases, and malignancies. Based on data, mortality due to heart failure reaches 50% in the first 5 years. Heart failure is responsible for 287,000 deaths per year. About half of people with heart failure die within five years of being diagnosed. The initial symptoms that commonly occur in patients with heart failure are dyspnea (shortness of breath), fatigue and fluid retention. Therapy for patients with heart failure includes non-pharmacological therapy and pharmacological therapy.